68Ga-PSMA-11 PET/CT in patients with recurrent prostate cancer: a modified protocol compared with the common protocol - Haupt, Fabian; Dijkstra, Lotte; Alberts, Ian; Sachpekidis, Christos; Fech, Viktor; Boxler, Silvan; Gross, Tobias; Holland-Letz, Tim; Zacho, Helle D.; Haberkorn, Uwe; Rahbar, Kambiz; Rominger, Axel; et al. (European journal of nuclear medicine and molecular imaging, 2020)
68Ga-PSMA-11 PET/CT is commonly performed at 1 h post injection (p.i.). However, various publications have demonstrated that most prostate cancer (PC) lesions exhibit higher contrast at later imaging. The aim of this study was to compare the “common” protocol of 68Ga-PSMA-11 PET/CT with a modified protocol.
Im Titel ist "68" in 68Ga-PSMA-11 PET/CT hochgestellt
Published online: 1 November 2019
Gesehen am 03.04.2020